Faktor Yang Mempengaruhi Kematian Neonatal Di Kabupaten Seluma - purnama sari kurniawati; Serilaila Serilaila; Maryani Maryani (JURNAL KEBIDANAN BESTARI, 2020)
Neonatal mortality rate in Bengkulu Province Year 2015 amounted to 8/1000 KH as well as in 2016 of 8/1000 KH. This nenonatal AKN is higher than Seluma Regency which has increased by 25% and this is lower than Kepahiang Regency (14/1000 KH), Bengkulu Tengah District (12/1000 KH). The purpose of this study was to determine the factors affecting neonatal mortality in Seluma District in 2016. The research is a descriptive analytic study with case control design. The study population of live-born infants in 2016 was 3338. The sample of the study of dead neonatal cases was 35 samples taken in total sampling. A sample of live neonatal control group of 126 was taken systematic random sampling.The results showed that there were correlation between education, age, parity, history of ANC mother and LBW with neonatal mortality in Seluma District in 2016. Furthermore, there was no correlation between birth spacing, labor and asphyxia with neonatal mortality in Seluma District in 2016. the effect on neonatal mortality is education, antenatal care dan LBW. Seluma District Health Office is expected to work with the Village Midwife in an effort to reduce the number of neonatal deaths by periodically providing KIE, APN training for midwives, improvement of ANC services and family planning services and infant care of LBW. Keywords: Education, Antenatal Care, Low Birth Weigt, Neonatal Death